Pogledi teologa in literarnega zgodovinarja Jožeta Rajhmana na slovenski katolicizem v reviji Znamenje - Reher, Srečko (Časopis za zgodovino in narodopisje, 2025)
In the paper The Views of the Theologian and Literary Historian Jože Rajhman on Slovenian Catholicism in the Journal Znamenje I present the Catholicism that church believers in Slovenia still encountered more than a decade and a half after the conclusion of the Second Vatican Council (1965). The shift towards the guidelines of the Second Vatican Council was represented by the establishment of the journal Znamenje in 1971, which was published until 2012. In it Jože Rajhman, a collaborator and member of the editorial board, published the greater part of his book opus. In his discussions he appears as an exceptional connoisseur of Slovenian and European Reformation, and as a perceptive researcher of the history of European and Slovenian spirituality and pastoral practice in our region. Rajhman judged the events in the Church from the horizons of the humanities and the new contextual theologies which, after the Second Vatican Council, confronted the concrete questions of the realization of evangelical Christianity.
Keywords: catechism-based faith; journal Znamenje; Jože Rajhman; katekizemska vernost; pokoncilski katolicizem; politični katolicizem; post-conciliar Catholicism; Protestantism; protestantizem; revija Znamenje; tradicionalno katolištvo; traditional Catholicism; verski fanatizem